Multiple meningiomas in different neuroaxial locations: report of a rare case - Sharma, Gopal Raman; Aryal, Sameer; Shrestha, Ramchandra; Deo, Alok; Pathak, Rakesh (Nepal Mediciti Medical Journal, 2021)
We report a rare case of multiple meningiomas in a 74 year old female who was brought to the hospital with spastic paraparesis and MRI of spine and brain revealed multiple enhancing meningiomas in brain and spines. The spinal intradural extramedullary (IDEM) meningioma at C7-D1 level was excised which had caused paraparesis and postoperatively patient became symptom free. We will discuss about the incidence, symptomatology, investigations and management of multiple meningiomas in different neuroaxial compartments at the same period of time and will review the literature.